2017
DOI: 10.2495/ut170181
|View full text |Cite
|
Sign up to set email alerts
|

Urban Mobility and Influence Factors: A Case Study of Prague

Abstract: Walking is the most natural human movement. A lack of walking on a daily basis causes a number of lifestyle diseases including diabetes, obesity and cardiovascular diseases. These medical complications are increasingly widespread by urban lifestyle. Comfort of non-physical activity allowed by developed transportation systems leads to the pandemic of physical passivity. Our case study is based on the data set of daily activity schedules of 89,948 urban citizens extracted from agent-based simulation model of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…As one of the major sources of pollutants in our cities is road traffic (Steele, 2001), reducing it would be an effective strategy to improve urban livability and their inhabitants' health. For example, several studies have proven that pedestrianization has a positive impact on health (Sobková and Čertickỳ, 2017;Soni and Soni, 2016;Tobon et al, 2018;Ward, 2010). Consequently, many cities have started to shift toward non-car friendly access (Parajuli and Pojani,2 Irene Lebrusán, Jamal Toutouh 2018; Sobková and Čertickỳ, 2017;Tobon et al, 2018;Ward, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the major sources of pollutants in our cities is road traffic (Steele, 2001), reducing it would be an effective strategy to improve urban livability and their inhabitants' health. For example, several studies have proven that pedestrianization has a positive impact on health (Sobková and Čertickỳ, 2017;Soni and Soni, 2016;Tobon et al, 2018;Ward, 2010). Consequently, many cities have started to shift toward non-car friendly access (Parajuli and Pojani,2 Irene Lebrusán, Jamal Toutouh 2018; Sobková and Čertickỳ, 2017;Tobon et al, 2018;Ward, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this way walking is incorporated in people’s everyday transport routines. A recent case study in Prague showed that daily walking routines – such as the walk from home to the public transport station and the walk from the car park to the workplace and back – covered, on average, 85.4% of people’s daily walking activity (Sobková and Čertický, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Databases containing the data categories indicated in Table 1 can provide data to examine the influence of sex, age [40] and BMI on ordinary daily physical activity of the population.…”
Section: Physical Activity Researchmentioning
confidence: 99%